Pengaruh Rasio Pasar Dan Rasio Profitabilitas Terhadap Return Saham Terhadap Perusahaan Perhotelan - Khaq, Muhammad Aunul; Susyanti, Jeni; Hardaningtyas, Ratna Tri (UNIVERSITAS ISLAM MALANG, 2024)
Abstract The objectives of this research are: 1) To examine the information content of market ratios and profitability ratios in hotel companies, 2) To determine the influence of market ratios and profitability ratios in hotel companies.The population of this research are companies listed on the Indonesian Stock Exchange (BEI), especially in the hospitality sector. This research method uses quantitative methods. The test equipment used in this research uses the SPSS application. In collecting samples using the documentation method through reports on the company website and also on the IDX. Based on the existing criteria, 9 hotel companies were obtained as research samples on the IDX in the 2019-2022 period.In this study, the t test was used which shows that market ratios have a significant effect on stock returns and profitability ratios do not have a significant effect on stock returns. Keywords: Market Ratios, Profitability Ratios, SPSS, BEI, Stock Returns, Shares.